2013
DOI: 10.3189/2013jog12j192
|View full text |Cite
|
Sign up to set email alerts
|

The effects of El Niño and La Niña on snow and avalanche patterns in British Columbia, Canada, and central Chile

Abstract: ABSTRACT. El Niñ o and La

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…Summarizing the nature of avalanche hazard this way has the potential to open new opportunities for studying the effects of large-scale climate oscillations and climate change on avalanche hazard that complements the perspectives of existing research in this area. Most of the existing studies on the effect of atmospheric oscillations on avalanche hazard (Dixon et al, 1999;Fitzharris, 1987;Keylock, 2003;McClung, 2013;Reardon et al, 2008;Thumlert et al, 2014) and climate change on avalanche hazard (Bellaire et al, 2016;Castebrunet et al, 2012;Jamieson et al, 2017;Laternser and Schneebeli, 2002;Lazar and Williams, 2008;Sinickas et al, 2016) have focused on examining trends in historical avalanche activity records. While avalanche activity along transportation corridors is tightly monitored, variations in avalanche control practices can make it difficult to attribute observed changes to long-term changes in winter weather conditions (Bellaire et al, 2016;Jamieson et al, 2017;Sinickas et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Summarizing the nature of avalanche hazard this way has the potential to open new opportunities for studying the effects of large-scale climate oscillations and climate change on avalanche hazard that complements the perspectives of existing research in this area. Most of the existing studies on the effect of atmospheric oscillations on avalanche hazard (Dixon et al, 1999;Fitzharris, 1987;Keylock, 2003;McClung, 2013;Reardon et al, 2008;Thumlert et al, 2014) and climate change on avalanche hazard (Bellaire et al, 2016;Castebrunet et al, 2012;Jamieson et al, 2017;Laternser and Schneebeli, 2002;Lazar and Williams, 2008;Sinickas et al, 2016) have focused on examining trends in historical avalanche activity records. While avalanche activity along transportation corridors is tightly monitored, variations in avalanche control practices can make it difficult to attribute observed changes to long-term changes in winter weather conditions (Bellaire et al, 2016;Jamieson et al, 2017;Sinickas et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…[ Beniston , ; Adam et al , ; Bebi et al , ; Keiler et al , ; Stoffel and Huggel , ]. Climate change is therefore likely to influence the occurrence of damage due to avalanches; however, the exact trend remains undecided and will be highly dependent on the region concerned [ Lavigne et al , ; Castebrunet et al , ; McClung , ]. Some studies have concluded that there is no clear correlation between the frequency of extreme events and climatic conditions [ Schneebeli et al , ; Eckert et al , ], whereas others have provided evidence that the runout distance of extreme avalanches has decreased since the mid‐1970s [ Eckert et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…Rutllant and Fuenzalida, 1991;Escobar and others, 1995;Leiva, 1999;Montecinos and Aceituno, 2003;Garreaud and others, 2009;Gascoin and others, 2011;Mernild and others, 2015). ENSO events have also been linked to increases in winter snowfall and a higher frequency of avalanches in the central Chilean Andes (Masiokas and others, 2006;McClung, 2013). Evidence suggests that precipitation patterns in the central Chilean and Argentinean Andes have undergone significant changes over the past ∼30 year (Pellicciotti and others, 2007).…”
Section: Introductionmentioning
confidence: 99%